Effect of cow manure on instead mon the growth of water spinach in gold mine tailings - Putri, Nadia Alifa; Hindersah, Reginawanti; Suryatmana, Pujawati (Current Research in Agricultural Sciences, 2023)
Gold mining activities produce abundant tailings waste. The negative impacts of tailing pollution on agriculture include soil profile loss, soil compaction, depletion of essential nutrients, organic matter, and soil pH, making it difficult for plants to grow. Cow manure (CM) is a well-known soil amendment to improve soil quality and facilitate root growth. Animal manure fertilizers contain a complete range of macro and micronutrients required by plants. In addition to its ability to enhance soil fertility, CM can also promote plant growth in former mining areas or mineral tailings. The objective of this study was to determine the effect of CM application rates on water spinach plant growth improvement. The experimental design used was a Completely Randomized Block Design (CRBD) with four treatments and six replications. The experimental treatments consisted of a control (without treatment), 10 t ha-1, 20 t ha-1, and 30 t ha-1 of CM. The results of the experiment showed that CM application increased plant height, leaf count, stem diameter, and wet weight of water spinach plants. The application of 10 t ha-1 CM showed the highest growth improvement in terms of plant height, leaf count, stem diameter, and wet weight of plants grown in gold mining tailings compared to other treatments. This experiment highlights the importance of CM for water spinach cultivation in tailing areas.